2004
DOI: 10.1002/adic.200490118
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Petroleum‐Contaminated Surface Soils in Serbia

Abstract: Investigation of heavy metal contamination levels as well as their association types with substrates in petroleum-contaminated surface soil was carried out using modified sequential extraction method. In that way, remobilization capacity of metal cations, both in natural conditions and in accidents, has been studied. Moreover, partitioning of heavy metals, originating from spilt oil derivative, among surface soil substrates was estimated. Extreme contamination with lead was discovered, as well as the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our results converged with Grujic et al (2004) who reported contamination of Pb, Cu, and Zn while investigating heavy metals in petroleum-contaminated surface soils of Serbia. Our results also corroborated the salient findings of Gondal et al (2006), where laser induced breakdown spectroscopy revealed the presence of several trace elements in the residue of crude oil samples.…”
Section: Soil Tph and Elemental Concentrationssupporting
confidence: 95%
“…Our results converged with Grujic et al (2004) who reported contamination of Pb, Cu, and Zn while investigating heavy metals in petroleum-contaminated surface soils of Serbia. Our results also corroborated the salient findings of Gondal et al (2006), where laser induced breakdown spectroscopy revealed the presence of several trace elements in the residue of crude oil samples.…”
Section: Soil Tph and Elemental Concentrationssupporting
confidence: 95%
“…A reduction in the soil pH to slightly acidic and acidic increases the mobility of trace elements and their availability for plants and soil microorganisms [ 65 ]. In particular, high mobility is exhibited by cadmium, even in soils with a neutral and slightly alkaline pH [ 65 ] and in those accumulated with oil-derivative substances [ 66 ]. Cadmium is a more mobile element in soil and also more strongly taken by plants, compared to many other trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…The effects noted for the other elements were not that obvious. According to Grujić et al [ 60 ], in soil contaminated with petroleum derivatives, nickel is bound with manganese oxides, which can be easily reduced, becoming the predominating source of this element in the topsoil. Wyszkowski and Sivitskaya [ 61 ] demonstrated a similar effect of soil contamination with fuel oil, which has similar properties to diesel oil, on the contents of chromium, lead and manganese in soil.…”
Section: Discussionmentioning
confidence: 99%